1978
DOI: 10.1128/jb.133.1.306-319.1978
|View full text |Cite
|
Sign up to set email alerts
|

Immunochemical analysis of inner and outer membranes of Escherichia coli by crossed immunoelectrophoresis

Abstract: Isolated membrane fractions of Escherichia coli K-12 yielded complex immunoprecipitate patterns when Triton X-100 and sodium dodecyl sulfate extracts were examined by crossed immunoelectrophoresis with antienvelope immunoglobulins. Twelve of the 46 antigens in the immunoprecipitate patterns of inner (plasma) membranes were identified by zymograms and/or by the use of specific antisera. The following enzyme activities were detected in immunoprecipitates: 6-phosphogluconate dehydrogenase (EC 1.1.1.43); adenosine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
32
0

Year Published

1979
1979
1999
1999

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…Additional chromatophore polypeptide components have been observed in sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) (6,15, 19), but the function of these components has remained largely unknown because this procedure results in the loss of any biological activity. Recently, crossed immunoelectrophoresis (CIE) has been applied to the study of bacterial membranes (7,14,17,18). Since nondenaturing detergents are used for membrane disruption before CIE, both enzymatic and antigenic activities are usually retained, thus permitting a functional analysis of membrane components.…”
mentioning
confidence: 99%
“…Additional chromatophore polypeptide components have been observed in sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) (6,15, 19), but the function of these components has remained largely unknown because this procedure results in the loss of any biological activity. Recently, crossed immunoelectrophoresis (CIE) has been applied to the study of bacterial membranes (7,14,17,18). Since nondenaturing detergents are used for membrane disruption before CIE, both enzymatic and antigenic activities are usually retained, thus permitting a functional analysis of membrane components.…”
mentioning
confidence: 99%
“…In addition to staining the CIE plates for heme, zymograms were also made for the most common dehydrogenases, as previously reported (27,36). Precipitin arcs were identified which contained residual D-lactate, succinate, and NADH dehydrogenase activities.…”
Section: Discussionmentioning
confidence: 98%
“…One purpose of this paper is to demonstrate the utility of both isoelectric focusing (IEF) and crossed immunoelectrophoresis (CIE) for the resolution and analysis of the E. coli cytochromes. Both techniques have been previously applied successfully to the study of membrane proteins (14,26,27,36). In our study, four heme-containing protein complexes were resolved under nondenaturing conditions in the presence of Triton X-100.…”
mentioning
confidence: 99%
“…Recently, attention is focussed on the possible use of outer membrane protein, particularly porins, as subunit vaccines against S. typhi, S. typhimurium, Escherichia coli, Pseudomonas aeruginosa, etc. (17,19,27,34). Results showed that they are good immunogens.…”
mentioning
confidence: 99%